A Changing Light Environment Induces Significant Lateral CO[sub.2] Diffusion within Maize Leaves - Wu, Han-Yu; Zou, Qing-Qing; Ji, Wen-Tao; Wang, Ying-Wei; Zhang, Wang-Feng; Jiang, Chuang-Dao (International journal of molecular sciences, 2022)
A leaf structure with high porosity is beneficial for lateral CO[sub.2] diffusion inside the leaves. However, the leaf structure of maize is compact, and it has long been considered that lateral CO[sub.2] diffusion is restricted. Moreover, lateral CO[sub.2] diffusion is closely related to CO[sub.2] pressure differences (ΔCO[sub.2]). Therefore, we speculated that enlarging the ΔCO[sub.2] between the adjacent regions inside maize leaves may result in lateral diffusion when the diffusion resistance is kept constant. Thus, the leaf structure and gas exchange of maize (C[sub.4]), cotton (C[sub.3]), and other species were explored. The results showed that maize and sorghum leaves had a lower mesophyll porosity than cotton and cucumber leaves. Similar to cotton, the local photosynthetic induction resulted in an increase in the ΔCO[sub.2] between the local illuminated and the adjacent unilluminated regions, which significantly reduced the respiration rate of the adjacent unilluminated region. Further analysis showed that when the adjacent region in the maize leaves was maintained under a steady high light, the photosynthesis induction in the local regions not only gradually reduced the ΔCO[sub.2] between them but also progressively increased the steady photosynthetic rate in the adjacent region. Under field conditions, the ΔCO[sub.2], respiration, and photosynthetic rate of the adjacent region were also markedly changed by fluctuating light in local regions in the maize leaves. Consequently, we proposed that enlarging the ΔCO[sub.2] between the adjacent regions inside the maize leaves results in the lateral CO[sub.2] diffusion and supports photosynthesis in adjacent regions to a certain extent under fluctuating light.